Mitral valve surgery for mitral regurgitation caused by Libman-Sacks endocarditis: a report of four cases and a systematic review of the literature - Bijl Marc; Erasmus Michiel E; Wijdh-den Hamer Inez J; van der Horst Iwan CC; Klinkenberg Theo J; Bouma Wobbe; Suurmeijer Albert JH; Zijlstra Felix; Mariani Massimo A (Journal of Cardiothoracic Surgery, 2010)
Abstract Libman-Sacks endocarditis of the mitral valve was first described by Libman and Sacks in 1924. Currently, the sterile verrucous vegetative lesions seen in Libman-Sacks endocarditis are regarded as a cardiac manifestation of both systemic lupus erythematosus (SLE) and the antiphospholipid syndrome (APS). Although typically mild and asymptomatic, complications of Libman-Sacks endocarditis may include superimposed bacterial endocarditis, thromboembolic events, and severe valvular regurgitation and/or stenosis requiring surgery. In this study we report two cases of mitral valve repair and two cases of mitral valve replacement for mitral regurgitation (MR) caused by Libman-Sacks endocarditis. In addition, we provide a systematic review of the English literature on mitral valve surgery for MR caused by Libman-Sacks endocarditis. This report shows that mitral valve repair is feasible and effective in young patients with relatively stable SLE and/or APS and only localized mitral valve abnormalities caused by Libman-Sacks endocarditis. Both clinical and echocardiographic follow-up after repair show excellent mid- and long-term results.